In vivo Evaluation of a Newly Synthesized Acetylcholinesterase Inhibitor in a Transgenic Drosophila Model of Alzheimer’s Disease - Uras, Giuseppe; Manca, Alessia; Zhang, Pengfei; Markus, Zsuzsa; Mack, Natalie; Allen, Stephanie; Bo, Marco; Xu, Shengtao; Xu, Jinyi; Georgiou, Marios; Zhu, Zheying (Frontiers in Neuroscience, 2021)
Alzheimer’s disease is a neurodegenerative disease characterised by disrupted memory and learning functions, as a result of the accumulation and aggregation of amyloid peptides that cause neuronal damage in neuronal circuits. In the current study, we exploited transgenic amyloid Drosophila melanogaster to investigate the efficacy of a newly synthesized acetylcholinesterase inhibitor, named XJP-1, as potential AD therapy. Behavioural assays and confocal microscopy were used to characterize the drug effect on AD symptomatology and amyloid peptides deposition. The symptomatology induced in this particular transgenic model recapitulates the scenario observed in human AD patients, showing a shortened lifespan and reduced locomotive functions, along with a significant accumulation of amyloid plaques in the brain. XJP-1 treatment resulted in a significant improvement of AD symptoms, reduction of amyloid plaques by diminishing the amyloid aggregation rate. In comparison with the clinically effective AD drugs, our results demonstrated that XJP-1 has similar effects on AD symptomatology at 10 times lower drug concentration than donepezil, and also showed earlier beneficial effect on reduction of amyloid plaques at 10 days after drug treatment than donepezil at 20 days, while others have no such effect. As a novel and potent AChE inhibitor, our study demonstrates that inhibition of AChE enzyme by XJP-1 treatment improves the amyloid-induced symptomatology in Drosophila, by reducing the number of amyloid plaques within the fruit fly CNS. Thus, compound XJP-1 has the therapeutic potential to be further investigated for the treatment of AD.